ESTUDO MICROBIOLÓGICO EM CARCAÇAS BOVINAS E INFLUÊNCIA DA REFRIGERAÇÃO SOBRE A MICROBIOTA CONTAMINANTE - Fontoura, C.l. [UNESP]; Rossi, O.d. [UNESP]; Martineli, T.m. [UNESP]; Cereser, N.d. [UNESP] (Instituto Biológico, 2020)
With the aim of evaluating the presence of microorganisms in bovine carcasses and the influence of refrigeration on the contaminating microbiotics, some samples were collected from the outer surface of half-carcasses in these regions (rump, loin and rib), after washing and after 24 hours under refrigeration. The average of the mesophilic heterotrofic, psychrotrofic andStaphylococcusmicroorgarnisms, obtained immediately after the carcass washing were respectively 1.8 x 10, 6.4 x 10 and 3.5 x 10 CFU/cm2, while for the samples collected after refrigeration these values were 1.3 x 10, 1.6 x 102 and 5.2 x 10 CFU/cm2. The populations were considered low due to the hygienic practices during the slaughter process, and the differences observed between the averages of the two groups of samples were not statistically significant, leading to the conclusion that that was not an increase of the microorganism population, thus demonstrating the efficacy of the refrigeration process after the slaughter.

Objetivando avaliar a presença de micro-organismos indicadores e de estafilococos em carcaças bovinas e a influência da refrigeração sobre a microbiota contaminante, foram analisadas amostras de regiões da superfície externa de meias carcaças tais como coxão, lombo e ponta-deagulha, logo após a lavagem e após 24 horas sob refrigeração. As médias das populações de microorganismos heterotróficos mesófilos, psicrotróficos e Staphylococcus sp. em UFC/cm2 obtidas imediatamente após a lavagem apresentaram valores respectivamente de 1,8 x 10, 6,4 x 10 e 3,5 x 10 UFC/cm2, enquanto que para as amostras colhidas após refrigeração os valores foram de 1,3 x 10, 1,6 x 102 e 5,2 x 10 UFC/cm2. As populações foram consideradas reduzidas, decorrentes de eficientes cuidados higiênicos sanitários durante as operações de abate, e as diferenças observadas entre as médias dos dois grupos de amostras não foram significativas do ponto de vista estatístico, o que permite concluir que não houve aumento considerável da população microbiana, demonstrando a eficiência do processo de refrigeração em seguida ao abate.
MICROBIOLOGICAL STUDY IN BOVINE CARCASSES AND THE INFLUENCE OF REFRIGERATION ON CONTAMINATING MICROBIOTA
Keywords: Bovine carcass; indicator microorganisms; Staphylococcus sp.; refrigeration; Carcaça bovina; micro-organismos indicadores; Staphylococcus sp.; refrigeração